Perineal groove. - Milano, A. (European Journal of Pediatric Dermatology, 2015)
The perineal groove is a rare congenital anomaly that affects almost exclusively the female sex and consists of a wet area because covered by mucosa. It is located on the perineal raphe between the posterior vaginal fork and the anus. There are several hypotheses regarding its pathogenesis: according to Mullassery et Al. (2) it could be an embryonic remnant of the urorectal septum; the Authors base their assumptions on the histology finding of rectal mucosa that covers the perineal groove. The perineal groove spontaneously tends to be covered by epidermis, usually within the second year of life. For this reason the surgical intervention should be proposed only after this age when the disorder does not tend to normalize spontaneously. In case of surgery it is necessary to cover the suture with special glues to prevent its dehiscence (1).